Ocular manifestations in Leigh syndrome - Kyo Ryung Kim; Suk Ho Byeon; Young Mock Lee; Hoon Chul Kang; Joon Soo Lee; Heung Dong Kim (Korean Pediatric Society, 2010)
Purpose : Leigh syndrome is a typical type of mitochondrial disease. This study was conducted to analyze the types of ophthalmologic symptoms and results of funduscopy conducted in the ophthalmologic examination of patients with Leigh syndrome. Methods : Funduscopy was conducted on 24 subjects, who were chosen among those diagnosed as having mitochondrial respiratory chain complex defect and who were clinically suitable for the criteria of Leigh syndrome. Their clinical features, ophthalmologic symptoms, and ophthalmologic examination results were retrospectively analyzed. Results : Of the 24 patients with Leigh syndrome, 11 developed ophthalmologic symptoms and no abnormal finding was observed in 13. The most frequent abnormal finding was visual disturbance in 5 patients. Funduscopy revealed abnormal findings in 17 patients; retinal pigmentation was the most frequent abnormality and was seen in 9 patients. Conclusion : Funduscopy can be an important screening test to find ophthalmologic abnormalities among patients with mitochondrial disease (MD), including those patients whose ophthalmologic symptoms are inconspicuous. It is predicted that an improved screening test can be made in the future that will identify risk factors related to ophthalmologic symptoms.